One-Third of European Patients With Axial Spondyloarthritis Reach Pain Remission With Routine Care Tumor Necrosis Factor Inhibitor Treatment - Ørnbjerg, Lykke Midtbøll; Rugbjerg, Kathrine; Georgiadis, Stylianos; Rasmussen, Simon Horskjær; Lindström, Ulf; Pavelka, Karel; Yilmaz, Neslihan; Favalli, Ennio Giulio; Nissen, Michael J; Michelsen, Brigitte; Vieira-Sousa, Elsa; Jones, Gareth T; et al. (The Journal of rheumatology, 2023)
OBJECTIVE: To investigate the distribution of patient-reported outcomes (PROs) in patients with axial spondyloarthritis (axSpA) initiating a tumor necrosis factor inhibitor (TNFi), to assess the proportion reaching PRO "remission" across registries and treatment series, and to compare patients registered to fulfill the modified New York (mNY) criteria for ankylosing spondylitis (AS) vs patients with nonradiographic axSpA (nr-axSpA). METHODS: Fifteen European registries contributed PRO scores for pain, fatigue, patient global assessment (PtGA), Bath Ankylosing Spondylitis (AS) Disease Activity Index (BASDAI), Bath AS Functional Index (BASFI), and Health Assessment Questionnaire (HAQ) from 19,498 patients with axSpA. Changes in PROs and PRO remission rates (definitions: ≤ 20 mm for pain, fatigue, PtGA, BASDAI, and BASFI; ≤ 0.5 for HAQ) were calculated at 6, 12, and 24 months of treatment. RESULTS: Heterogeneity in baseline characteristics and outcomes between registries were observed. In pooled data, 6 months after the start of a first TNFi, pain score was reduced by approximately 60% (median at baseline/6/12/24 months: 65/25/20/20 mm) in patients on treatment. Similar patterns were observed for fatigue (68/32/30/25 mm), PtGA (66/29/21/20 mm), BASDAI (58/26/21/19 mm), BASFI (46/20/16/16 mm), and HAQ (0.8/0.4/0.2/0.2). Patients with AS (n = 3281) had a slightly better response than patients with nr-axSpA (n = 993). The Lund Efficacy Index (LUNDEX)-adjusted remission rates at 6 months for pain/fatigue/PtGA/BASDAI/BASFI/HAQ were 39%/30%/38%/34%/35%/48% for the AS cohort and 30%/21%/26%/24%/33%/47% for the nr-axSpA cohort. Better PRO responses were seen with a first TNFi compared to a second and third TNFi. CONCLUSION: Patients with axSpA starting a TNFi achieved high PRO remission rates, most pronounced in those fulfilling the mNY criteria and for the first TNFi.
Keywords: Spondylarthritis; tumor necrosis factor inhibitors; únava; Non-Radiographic Axial Spondyloarthritis; výsledek terapie; Tumor Necrosis Factor-alpha; non-radiografická axiální spondyloartritida; Pain; Fatigue; axial spondyloarthritis; ankylózující spondylitida; TNF-alfa; patient-reported outcome measures; Spondylitis, Ankylosing; Humans; spondylartritida; inhibitory TNF; Tumor Necrosis Factor Inhibitors; bolest; Treatment Outcome; lidé